Differences in treatment choices for localised prostate cancer diagnosed in private and public health services. Issue 9 (30th September 2020) - te Marvelde, Luc; Milne, Roger L; Hornby, Colin J; Chapman, Adam B; Giles, Graham G; Haines, Ian E
Abstract: Objective: To compare treatments for localised prostate cancer for men diagnosed in private and public health services in Victoria. Design: Retrospective analysis of Victorian Cancer Registry data linked to population‐based administrative health datasets. Setting, participants: 29 325 Victorian men diagnosed with prostate cancer during 2011–2017. Main outcome measures: Proportions of men in private and public health services receiving radical prostatectomy (with or without curative radiation therapy) or curative external beam radiation therapy alone within 12 months of diagnosis. Results: After adjusting for age, tumour classification and comorbidity, men diagnosed in private health services received radical treatment more frequently than men diagnosed in public health services (odds ratio [OR], 1.40; 95% confidence interval [CI], 1.31–1.49). The proportion of private patients who underwent radical prostatectomy was larger than that for public patients (44% v 28%; OR, 2.28; 95% CI, 2.13–2.44) and the proportion of private patients who received curative external beam radiation therapy alone (excluding brachytherapy) was smaller (9% v 19%; OR, 0.45; 95% CI, 0.42–0.49). These differences were apparent for all International Society of Urological Pathology (ISUP) tumour grades. The magnitude of the difference for prostatectomy was greater for men aged 70 years or more; for radiation therapy alone, it was larger for those diagnosed before age 70. The differences between private and public services narrowed during 2011–2017 for men with ISUP grade 1 disease, but not ISUP grade 2–5 tumours. Conclusion: Prostate cancer treatment choices differ substantially between men diagnosed in private and public health services in Victoria. These differences are not explained by disease severity or comorbidity.